2022
DOI: 10.1101/2022.07.31.502217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacologic Stabilization of Retromer Rescues Endosomal Pathology Induced by Defects in the Alzheimer’s geneSORL1

Abstract: Defects in the Sortilin-related receptor 1 gene, SORL1, are highly pathogenic in Alzheimer's disease (AD), on par with other causal AD genes. SORL1 is a key regulator of endosomal trafficking in neurons, and loss of SORL1 function disrupts trafficking pathways that are vital for neuronal health. SORL1 has been found to interact with retromer, a protein complex that is a 'master conductor' of endosomal trafficking. Here we rely on retromer pharmacological chaperones that stabilize retromer in vitro, and thus en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…We next examined iPSC-derived neurons that harbor a SORL1 mutation, Gly511Arg, originally identified in a mother and daughter who each had early-onset AD 3 along with paired isogenic SORL1 WT neurons. 45 As in SORL1 KO iNs, heterozygous G115R mutation of SORL1 was sufficient to induce a reduction in APOE and CLU in neurons ( Figures 7L – 7P ). In addition, lipidomic profiling of G511R iNs revealed three classes of lipids that showed concordant dysregulation with SORL1 KO iNs: DG, HexCer, and Hex3Cer ( Figures 7Q – 7T ).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…We next examined iPSC-derived neurons that harbor a SORL1 mutation, Gly511Arg, originally identified in a mother and daughter who each had early-onset AD 3 along with paired isogenic SORL1 WT neurons. 45 As in SORL1 KO iNs, heterozygous G115R mutation of SORL1 was sufficient to induce a reduction in APOE and CLU in neurons ( Figures 7L – 7P ). In addition, lipidomic profiling of G511R iNs revealed three classes of lipids that showed concordant dysregulation with SORL1 KO iNs: DG, HexCer, and Hex3Cer ( Figures 7Q – 7T ).…”
Section: Resultsmentioning
confidence: 71%
“…Description and characterization of SORL1 variant iPSCs containing heterozygous G511R variant have been previously published. 45 gRNA ‘CTCTTGCATTTTAGGCTCAG’ and G511R ssODN: CTGACATATTCTTGAAATTAAAAATAATTATTTCTCTTGCATTTTAGGCTCAGTGCGAAAGAACTTGGCTAGCAAGACAAACGTGTACATCTCTAGCAGTGCTGGAGCCAGGTGGCG was used to target VPS10p domain in iPSC line 1, which is the same iPSCs used to generate SORL1 KO iPSCs. The Zhang Lab CRISPR Design website ( crispr.mit.edu ) was used to generate guide RNAs (gRNAs) with minimal off-target effects.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore likely that iPSC neurons with pathogenic SORL1 missense variants will also have larger endosomes compared with wild-type cells, which suggests that studying endosomal size is an alternative method to determine SORL1 variant pathogenicity. A recent study has followed this strategy and demonstrated that indeed endosome structures are also increased in cells with different SORL1 missense variants [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retromer is a large protein complex which ‘rescues’ proteins from endosomes, targeting them to recycling instead of lysosomal digestion 76 . By disrupting retromer function, mutations in SORL1 disrupt endosomal recycling, which appears as swelling of early endosomes 77 . As a result, APP remains in endosomes for longer, where it is more likely to be cleaved by β-secretase, the first step towards production of Aβ 78 .…”
Section: Discussionmentioning
confidence: 99%